THEOLOGY AS A WAY OF LIFE. ON TEACHING AND LEARNING THE CHRISTIAN FAITH - M. Laubscher (Acta Theologica)
A review of Neder, A. (Grand Rapids, MI: Baker Academic, 2019) 158 pp. ISBN: 978-0-8010-9866-6 (R403)